IMPROVING THE RELIABILITY OF WORKING BODIES OF TILLAGE MACHINES - Дудніков, А. А.; Біловод, О. І.; Пасюта, А. Г. (Scientific Progress & Innovations, 2014)
The article discusses issues of increasing longevity and reliability of working bodies of tillers in the process of recovery (manufacturing) using vibrations that promote intensification processing methods, increase the level of mechanization and automation of many labor-intensive technologies. The dependence of the intensity of the vibration to strengthen the following factors: the mode of processing, physical and mechanical properties of the material machined parts. Found that the main process parameters of the vibration of hardening is the disturbing force exciter, the amplitude and frequency of oscillation of the machining tool, the speed and processing time.